Ethical issues and approaches in the behavioral task - Montgomery U., William (2017)
In this paper the issue of ethical behavior is addressed in its conceptual, methodological and technological aspects. Conceptually fundamental problems and explanatory mechanisms of moral behavior are discussed. At the methodological level one refers to ethics related to behavioral science itself, and another deals with ethics in relations between behavioral science and society. The technological level involves maintaining contact between experimental research and science-based technological practice and good probability of efficacy, while continuing to respect protocols and customer protection.